An Oirat literary collection from the Aldan-Maadyr National Museum of the Tuva Republic - Bicheev, Baazr A.; Bicheldey, Kaadyr-ool A. (The New Research of Tuva, 2019)
The article introduces into scientific discourse the text of one Oirat literary collection contained in the Aldan-Maadyr National Museum the Tuva Republic. This is the only known manuscript copy of the Oirat collection which includes two famous works related to the same literary genre — precepts or instructions (Mong. сургаал) — though essentially different. The first text is a small work which reveals a quintessence of the Buddhist teaching through a dialogue between the Buddha and a Brahmin. The story is referred to under different names, including as ‘The Tale of the Buddha and the Brahmin’. The text of this novel is known in its Clear Script version only, and currently there is no data regarding any Classical Mongolian versions. The second work is widely known in Old Mongolian literature as ‘The Tale of the Boy Riding the Black Bull’. In Oirat Clear Script literature, the text is known as ‘The Tale of the Three-Year-Old Boy’. The article provides a transliteration of the Oirat text accompanied by a Russian translation and respective comments.